Ionic polymer metallic composite as wearable impact sensor for sport science. (7th May 2010) - Chen, H.H.; Fang, S.C.; Aw, K.C.
Ionic polymer metallic composite (IPMC) is a type of ionic electroactive polymer that has electromechanical property that can be used as actuators or sensors. IPMC sensors offer several advantages over conventional sensors; such as flexibility, conformability and durability are useful for impact sensing. The aim of the paper is to demonstrate the ability of IPMC as an impact sensor to be used in sport science. The ability to measure impact force or energy is important in sport science as this information can be used to improve athletes' performances. In this research, experiments were conducted for different impact energies and a mathematical model based on the impact sensor's output voltage spike's slope was developed. Testing using this model demonstrated that the accuracy of the measured impact energy is mostly within ±10% although an error of up to 25% was observed at low impact energies.